Nos contornos do Eu: um estudo sobre a religiosidade nas neuroses e psicoses - Torres, Caroline Gonzaga (2013)
There is, in this dissertation, the purpose of discussing whether there is, from the point of view of the Ego structure in subjects, elements by which to discern what supports the way neurotics and psychotics demarcate distinct positioning in the face of religious experiences, establishing different relationships with divinity. Therefore, methodologically, to undertake a bibliographical study based on the work of Freud and Lacan, in the first teaching, in their productions concerning religion, constitution of Ego, neurosis and psychosis, beyond a discussion of two Freudian cases: Schreber and the Rats Man. So, take place joints between religion and father complex in psychoanalysis, addressing the elements present in the traumatic origin of monotheistic religions and the way they are updated in the subject, and set up approaches between religious formations, production delusional and fantasy. Makes up a theoretical framework on the mode ego structure, on the neuroses and psychoses, in stressing the concept of narcissism to establish the imaginary and symbolic dimensions that participate in this process as well as for the subsequent theoretical modifications. Finally, it is an investigation regarding the way in which the Ego is constituted in neuroses and psychoses, mechanisms peculiar to each of these structures and the presence of religious speech as well as of divine figures, by analysis of clinical cases. Among the main findings of the research highlight: a) intelligibility in Freudian formulations about religion, placing it sometimes beside the neuroses, sometimes beside the psychoses, giving her a double logic; b) the peculiarities in the constitution of the Ego, this is, fixing the paranoid in the mirror stage and the crossing of the obsessive at Oedipus, as well as their distinct attitudes towards Other and conflicts of these psychic structures instances, result a way in which the experiences of religion and deities appear in symptoms and elementary formations; c) the structural belief notion in neurosis and the dimension of certainty in psychosis allow in the perception of differences in the way these individuals understand the divine figures, which appear consistently associated with paternal figure in psychoanalytic theorizing.